The effects of Chamomile tea on antioxidative biomarkers in operating room staff - Sami Ghazal; Khoshraftar Ebrahim; Heidary Shayesteh Tavakol; Ranjbar Akram (Shahrekord University of Medical Sciences, 2015)
Introduction: Chamomile tea (CT) is an herbal tea and is served as a beneficial herbal infusion all over the world. Its major polyphenols constituents and tea-catechins have been shown to have health benefits. Operating room staff are commonly exposed to damaging factors, such as radiation, waste anesthetic gases and psychological stress. One of the most important qualities of CT is its antioxidant property. The aim of this study was to evaluate the effects of CT in reducing the oxidative stress of operative room staff that are chronically exposed to damaging factors. Methods: In this study we approached to 20 operating room personnel. The subjects drank 2 cups of CT (every cup contained 1.8730 g of chamomile and 300 ml of water) daily, one cup in the morning and another in the afternoon for 21 days. A questionnaire that contained personal information was filled by each subject. Oxidative stress parameters such as total antioxidant capacity (TAC), catalase (CAT) and total thiol molecules (TTG) were measured 2 times: first before drinking CT at the first day and the next time after the 21st day. Results: Consumption of CT by subjects caused a significant induction in TAC (6.62 ± 0.77 vs 4.81± 0.39 ųmol/ml, P < .05) of saliva. There was not any statistically significant change in saliva TTG and CAT after 21 days of drinking CT. Conclusion: In the end we came to conclusion that CT can be a useful additional food to remove the oxidative damage that happens to operating room staff.